Mapping the geography of cybercrime: a review of indices of digital offending by country - Lusthaus, J; Bruce, M; Phair, N (Institute of Electrical and Electronics Engineers, 2020)
The acknowledgement that cybercrime offenders are embedded within local contexts presents a broad vector for further study. But research in this area is still in its early days and many topics need to be developed further. Foremost among these is the geography of cybercrime. This endeavour has an important policy contribution to make. For example, if we can determine which countries are producing cybercrime at more significant levels, preventative measures can be specifically targeted to those countries. The first step within such a research agenda must be the development of an index of cybercriminality by country, as this is foundational to identifying hubs of digital offending and the factors driving the emergence of these hubs. This paper is methodological in its contribution, and does not offer its own empirical findings. Instead, it aims to provide some broad foundational thinking for a very challenging research exercise, and it is intended to support later, more refined, efforts to develop indices. It consists of two components. First, it reviews existing attempts to identify and rank cybercrime hotspots. Second, it draws important lessons from these works towards developing a successful index. Some methodological points are made on what the way forward may be for this emerging field, and how a reliable and valid index on cybercriminality could be crafted.